Pemphigus Foliaceous with special reference to Visphota Kushta (International Journal of Ayurveda and Pharma Research, 2024)
Pemphigus is an autoimmune blistering disease which can be fatal if left untreated. In case of secondarily infected skin lesions, life threatening sepsis may develop. There is no specific treatment protocol for the management of pemphigus. The present study is aimed to treat a 57-year-old male patient clinically diagnosed with pemphigus foliaceus admitted in Kayachikitsa department in Govt. Ayurveda College, Thiruvananthapuram. Treatment was aimed at controlling the progression of disease, preventing infection and inducing healing of the affected area. In Ayurveda symptoms are more similar to Kaphapitha kushta especially Visphota kushta. Langhana, Snehapana and repeated Sodhana were the treatment protocols adopted. Ayurvedic approach in this single case of pemphigus is beneficial in correcting the inherent Agnimandya at Koshta and Dhatu level and thus provides significant result. PDAI score was used for assessment. Before treatment PDAI was 96, reduced to 24 after Sodhana and after treatment it was 6. There was no recurrence of symptoms after 2 weeks.